Nudges to increase completion of welfare applications: Experimental evidence from Michigan - Christopher J. O'Leary; Dallas Oberlee; Gabrielle Pepin (W.E. Upjohn Institute for Employment Research, 2020)
The Temporary Assistance for Needy Families (TANF) program provides cash assistance to very-low-income families with children. Application procedures to receive TANF benefits, however, often involve substantial transaction costs likely to reduce take-up. We estimate, through a randomized controlled trial design, the effects of a detailed telephone-call reminder to increase TANF application completion in southwest Michigan, where applicants must visit a regional public employment office at least four times to be eligible for benefits. We do not find that personalizing reminder calls increased participation in the initial appointment at the public employment office. However, conditional on attending the initial session, applicants who received reminder calls before additional appointments were more likely to complete all application requirements, compared to those who did not receive reminders. Evidence suggests that reminder calls increase attendance at public employment office appointments but that personalizing such calls has limited impact.
Keywords: D90; I38; H75; H83; 330; Temporary Assistance for Needy Families; nudge; welfare-to-work; randomized controlled trial; application costs